Presurgical platelet–lymphocyte ratio for prognosis in advanced hypopharyngeal squamous cell carcinoma in individuals undergoing radical resection. (4th May 2021) - Chen, Hong; Song, Shenghua; Li, Ao; Ma, Dengbin; Lin, Chuanyao; Qian, Xiaoyun; Gao, Xia; Shen, Xiaohui
Abstract: Background: Patient prognosis in hypopharyngeal carcinoma remains difficult to predict, necessitating new, readily available biomarkers. Objective: Platelet–lymphocyte ratio (PLR)'s effects on recurrence-free survival (RFS) and overall survival (OS) were evaluated in individuals undergoing radical resection for advanced hypopharyngeal squamous cell carcinoma (HSCC). Methods: A total of 89 patients were retrospectively assessed. PLR, and derived neutrophil–lymphocyte (dNLR) and neutrophil–lymphocyte (NLR) ratios were determined based on complete blood count. Then, the prognostic values of PLR, dNLR and NLR were assessed by univariate and multivariate Cox regression analyses adjusted for disease-specific prognostic factors. Endpoints of interest were RFS and OS. Results: The optimal cutoff of PLR was 98.815, based on which individuals were categorized into the high- (PLR ≥98.815) and low- (PLR <98.815) PLR groups. High PLR ( p  = .022) had a significant association with reduced RFS, which still showed significance in multivariable analysis (HR = 2.020, 95%CI: 1.076–3.794, p  = .029). In univariate analysis, PLR ( p  = .046) and positive surgical margin ( p  = .021) also had significant associations with OS. Conclusion: Elevated PLR has associations with increased risk of recurrence and reduced survival in advanced HSCC cases undergoing radical resection. High presurgical PLR may independently predict RFS. Therefore, further multi-institutional prospective studies are needed to better characterize the role of pre-operative blood PLR as prognostic factors in HSCC.